Histology of portal vascular changes associated with idiopathic non‐cirrhotic portal hypertension: nomenclature and definition. Issue 2 (17th October 2018) - Guido, Maria; Alves, Venancio A F; Balabaud, Charles; Bathal, Prithi S; Bioulac‐Sage, Paulette; Colombari, Romano; Crawford, James M; Dhillon, Amar P; Ferrell, Linda D; Gill, Ryan M; Hytiroglou, Prodromos; Nakanuma, Yasuni; et al.
Abstract : Idiopathic non‐cirrhotic portal hypertension (INCPH) is a rare vascular liver disease that has attracted new interest in recent years. It is characterised by clinical signs of portal hypertension in the absence of cirrhosis or severe fibrosis and any known cause of portal hypertension. As much uncertainty exists about INCPH pathophysiology, and no definite diagnostic tests are available, liver biopsy is an essential tool for achieving a definite diagnosis. Unfortunately, the histological diagnosis of INCPH is not always straightforward, as the characteristic lesions are unevenly distributed, vary greatly in their severity, are often very subtle, and are not all necessarily present in a single case. Furthermore, specifically for the characteristic portal vessel changes observed in INCPH, the terminology and definition are ambiguous, which adds complexity to the already complex clinicopathological scenario. An international study group of liver pathologists and hepatologists pursued a consensus on nomenclature for the portal vascular lesions of INCPH. Such standardisation may assist pathologists in the recognition of such lesions, and will possibly facilitate further advancement in this field.